Missing Element of Consciousness? History from Below 10 Years after the Appel de Blois - Gęsiarz, Michał (Sensus Historiae, 2019)
The text discusses the history and characteristics of a movement known as history from below or people’s history. The first part discusses the development of this trend from the actions of Communist Party Historians Group in Great Britain to extending the research in geographical and social terms. In the next part, the most important features of history from below and its relations with traditional historiography and politics of memory were specified. The last two parts of the article deal with critical remarks about history from below and perspectives of its development in Poland with an indication of the last decade.